Household Pit Emptying and Reuse Practices in Rural Cambodia - World Bank (World Bank, Washington, DC, 2020)
Poor sanitation and hygiene practices remain a significant challenge for Cambodia. The purpose of this study is based on a request of the Ministry of Rural Development (MRD) to identify the behavior change gap as illustrated in fecal sludge management (FSM) in rural areas theory of change. Thus, the main purpose of this research study is to understand current practices of pit emptying and sludge reuse in the rural context of Cambodia and to find drivers and barriers of these pit emptying and sludge usage behaviors. The study is designed with a purpose to track the aspirations, motivations, and barriers impacting such practices in the rural context. Findings from this study is to produce a set of recommendations that can be an informed choice for the MRD to design a rural FSM national guideline. The findings from this study will also provide a key input for water, sanitation, and hygiene (WASH) sector of Cambodia with a comprehensive information and analysis as a catalyst to understand the views of FSM behaviors and practices from stakeholders, individual households, and private sectors for developing innovative solutions to address issues of FMS management and practice in the rural context.